2020
DOI: 10.3389/fmars.2020.00045
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Siderophore-Promoted and Reductive Dissolution of Dust in Marine Microenvironments Such as Trichodesmium Colonies

Abstract: Bio-Enhanced Dust Dissolution Fe-quotas and growth rates we calculated the Fe requirements of the colonies under Felimited and Fe-replete conditions. The calculated dissolved Fe supply from dust retained within colonies can fulfill the Fe requirements of slow growing Fe-limited colonies, but cannot support fast growth and/or higher cellular Fe quotas. We conclude that despite these bio-dissolution mechanisms, dust-Fe availability to Trichodesmium is low and propose that it employs additional mechanisms to acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 94 publications
1
10
0
Order By: Relevance
“…Recent research has also shown that some diatoms species can effectively “mine” and enhance dissolution of other particulate Fe phases that might not be quantified with the FeA extraction (Kessler et al, 2020; Rubin et al, 2011; Shoenfelt et al, 2017). For example, additions of Fe(II)‐rich glaciogenic dust from Patagonia have been shown to significantly enhance diatom growth in sFe‐limited culture experiments, compared to additions of Fe(III)‐rich non‐glaciogenic dust (Shoenfelt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has also shown that some diatoms species can effectively “mine” and enhance dissolution of other particulate Fe phases that might not be quantified with the FeA extraction (Kessler et al, 2020; Rubin et al, 2011; Shoenfelt et al, 2017). For example, additions of Fe(II)‐rich glaciogenic dust from Patagonia have been shown to significantly enhance diatom growth in sFe‐limited culture experiments, compared to additions of Fe(III)‐rich non‐glaciogenic dust (Shoenfelt et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is important because Trichodesmium thrives in regions where iron-rich continental dust is deposited such as the North Atlantic, Red Sea, and near landforms including Australia and the Caribbean islands [ 18 , 19 ]. Dust addition experiments, both in the laboratory and in shipboard incubations, have demonstrated that Trichodesmium puff colonies can selectively capture [ 20 ] and efficiently acquire iron from (oxy/hydro)oxide dust minerals [ 14 – 16 , 21 ] with the involvement of the epibiont community [ 22 , 23 ]. Dust particles can relieve iron stress and improve Trichodesmium’s metabolic function [ 24 , 25 ], but may also act as ballast leading to accelerated sinking of Trichodesmium colonies and enhanced carbon sequestration [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the $80-fold higher cellular requirements for P compared with Fe (San ˜udo- Wilhelmy et al, 2001Wilhelmy et al, , 2004. Despite the low overall solubility of both Fe and P from dust, typically estimated 0.1%-10% (Aguilar-Islas et al, 2010;Mahowald et al, 2005Mahowald et al, , 2008Stockdale et al, 2016), Trichodesmium can employ a variety of biochemical pathways and physical mechanisms in order to enhance the solubility and bioavailability of Fe from dust (Basu et al, 2019;Basu and Shaked, 2018;Eichner et al, 2019Eichner et al, , 2020Held et al, 2020a;Kessler et al, 2020b;Rubin et al, 2011). The effect of such mechanisms on dust-P solubility has not yet been studied, but as P is often associated with Fe, it is likely that Trichodesmium can also modify dust-P and enhance its bioavailability.…”
Section: Mineral-collection Ranking-trichodesmium Colonies Prefer Dust Over All Mineralsmentioning
confidence: 97%
“…The ability to remove particles provides flexibility with regards to the amount and type of particles colonies can retain. Such flexibility enables colonies to offset the potential negative effects of a high particle load such as buoyancy loss, exposure to toxic trace elements present in dust, increased visibility to predators, self-shading by particles, and restricted diffusion of solutes (Held et al, 2020a;Kessler et al, 2020b;Paytan et al, 2009;Walsby, 1992). An ability to remove particles also enables colonies to rapidly change their pool of particles and replace nutrient-exhausted particles with fresh ones, potentially providing larger nutrient fluxes.…”
Section: Optimization Of Particle Retention Within the Colony's Core Through Particle Removalmentioning
confidence: 99%
See 1 more Smart Citation